Construct validity of a figure rating scale for Brazilian adolescents - Adami, Fernando; Schlickmann Frainer, Deivis Elton; Almeida, Fernando de Souza; Abreu, Luiz Carlos de [UNESP]; Valenti, Vitor Engrácia [UNESP]; Piva Demarzo, Marcelo Marcos; de Mello Monteiro, Carlos Bandeira; de Oliveira, Fernando R. (Biomed Central Ltd., 2012)
Background: Figure rating scales were developed as a tool to determine body dissatisfaction in women, men, and children. However, it lacks in the literature the validation of the scale for body silhouettes previously adapted. We aimed to obtain evidence for construct validity of a figure rating scale for Brazilian adolescents.Methods: The study was carried out with adolescent students attending three public schools in an urban region of the municipality of Florianopolis in the State of Santa Catarina (SC). The sample comprised 232 10-19-year-old students, 106 of whom are boys and 126 girls, from the 5th series (i.e. year) of Primary School to the 3rd year of Secondary School. Data-gathering involved the application of an instrument containing 8 body figure drawings representing a range of children's and adolescents' body shapes, ranging from very slim (contour 1) to obese (contour 8). Weights and heights were also collected, and body mass index (BMI) was calculated later. BMI was analyzed as a continuous variable, using z-scores, and as a dichotomous categorical variable, representing a diagnosis of nutritional status (normal and overweight including obesity).Results: Results showed that both males and females with larger BMI z-scores chose larger body contours. Girls with higher BMI z-scores also show higher values of body image dissatisfaction.Conclusion: We provided the first evidence of validity for a figure rating scale for Brazilian adolescents.
Keywords: Body contour; Adolescents; Validity; Body image